2003
DOI: 10.1098/rsbl.2003.0033
|View full text |Cite
|
Sign up to set email alerts
|

Infection increases the value of nuptial gifts, and hence male reproductive success, in the Hymenolepis diminuta-Tenebrio molitor association

Abstract: During copulation, male insects pass accessory gland components to the female with the spermatophore. These gifts can affect female reproductive behaviour, ovulation and oviposition. Here, we show that female mealworm beetles, Tenebrio molitor, mated with males infected with metacestodes of the rat tapeworm, Hymenolepis diminuta, produced significantly more offspring than those mated with uninfected males. There is a significant positive relationship between parasite intensity in the male and reproductive outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
(26 reference statements)
1
14
1
Order By: Relevance
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18]. In our study, however, calling activity did not increase in all infected frogs; we found that infected frogs in relatively poor condition were less likely to call than uninfected frogs.…”
Section: Discussioncontrasting
confidence: 50%
“…For example, among female hosts, Tasmanian devils (Sarcophilus harrisii) infected by a transmissible cancer mature and breed earlier [12], and crickets (Acheta domesticus) infected by a bacterium, and water fleas (Daphnia magna) infected by a microsporidian lay more eggs [13,14]. Among male hosts, frogs (Lithobates pipiens) infected by a fungus increase sperm production [15], flies (Drosophila nigrospiracula) infected by a parasitic mite, and amphipods (Corophium volutator) infected by trematodes increase reproductive effort [16,17], and beetles (Tenebrio molitor) infected by tapeworms provide higher quality nuptial gifts to their mates, thus increasing egg production [18]. Whether hosts increase their reproductive effort in response to an infection depends on many factors, including resource availability [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, both human history and agricultural experience suggest that another type of interaction may also be critical: that between hosts and their parasites (e.g., Brown 2003;Cory and Myers 2004;Fitze et al 2004). For example, recent studies on a diverse array of taxa confirm that parasite infestation can modify the host's physiology (Kelly et al 2003;Rivero and Ferguson 2003;Simon et al 2004), behaviour (Dezfuli et al 2003;Field et al 2003;Fitze et al 2004;Vala et al 2004), developmental trajectories (Bize et al 2003), ecology (Snoeijs et al 2004), life-history schedules (Guinnee et al 2003;Neuhaus 2003;Fargallo and Merino 2004;Guinnee and Moore 2004;Madsen et al 2005), and reproductive success (Hurd and Ardin 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In the mealworm beetle, parasites are shown to increase male reproductive success (Hurd and Ardin 2003) and lifespan (Hurd et al 2001), and decrease level of sexual signaling (Worden et al 2000). Novel immune challengers have been shown to increase the level of sexual signaling ) and decrease lifespan (Armitage et al 2003).…”
Section: Discussionmentioning
confidence: 98%